The Grad Cohort Workshop: Evaluating an Intervention to Retain Women Graduate Students in Computing - Stout, Jane G.; Tamer, Burçin; Wright, Heather M.; Clarke, Lori A.; Dwarkadas, Sandhya; Howard, Ayanna M. (Frontiers in Psychology, 2017)
Women engaged in computing career tracks are vastly outnumbered by men and often must contend with negative stereotypes about their innate technical aptitude. Research suggests women’s marginalized presence in computing may result in women psychologically disengaging, and ultimately dropping out, perpetuating women’s underrepresentation in computing. To combat this vicious cycle, the Computing Research Association’s Committee on the Status of Women in Computing Research (CRA-W) runs a multi-day mentorship workshop for women graduate students called Grad Cohort, which consists of a speaker series and networking opportunities. We studied the long-term impact of Grad Cohort on women Ph.D. students’ (a) dedication to becoming well-known in one’s field, and giving back to the community (professional goals), (b) the degree to which one feels computing is an important element of “who they are” (computing identity), and (c) beliefs that computing skills are innate (entity beliefs). Of note, entity beliefs are known to be demoralizing and can lead to disengagement from academic endeavors. We compared a propensity score matched sample of women and men Ph.D. students in computing programs who had never participated in Grad Cohort to a sample of past Grad Cohort participants. Grad Cohort participants reported interest in becoming well-known in their field to a greater degree than women non-participants, and to an equivalent degree as men. Also, Grad Cohort participants reported stronger interest in giving back to the community than their peers. Further, whereas women non-participants identified with computing to a lesser degree than men and held stronger entity beliefs than men, Grad Cohort participants’ computing identity and entity beliefs were equivalent to men. Importantly, stronger entity beliefs predicted a weaker computing identity among students, with the exception of Grad Cohort participants. This latter finding suggests Grad Cohort may shield students’ computing identity from the damaging nature of entity beliefs. Together, these findings suggest Grad Cohort may fortify women’s commitment to pursuing computing research careers and move the needle toward greater gender diversity in computing.